Microbiota is structured by gut regions, life stage, and diet in the Black Soldier Fly (Hermetia illucens) - Auger, Laurence; Deschamps, Marie-Hélène; Vandenberg, Grant; Derome, Nicolas (Frontiers in Microbiology, 2023)
Black soldier fly (Hermetia illucens) larvae offer many ecological services that resulted in significant commercial development, bioconverting low value waste into high value feed and soil amendments. Understanding how the bacterial and eukaryote microbiota communities affect host performance becomes vital for the optimization and specialization of industrial scale rearing. This study investigates H. illucens associated microbiota taxonomic composition and dynamics across the developmental cycle (eggs, neonates, larvae, prepupae and imago X0 to second generation X1) when reared on two substrates: i) plant based (Housefly Gainesville diet) and ii) animal based (poultry hatchery waste). Using 16S gene amplicon metataxonomic approach, results revealed how bacterial microbiota inherited from parents reared in a different substrate may have induced dysbiosis in the progeny, as interaction networks of hatchery waste reared individual showed a high prevalence of negative interactions and low connectivity. Plant based feed reared black soldier flies’ microbiota was dominated by the phyla Proteobacteria (39-92%), Firmicutes (4-39%), Bacteroidota (1-38%) and Actinobacteria (1-33%). In animal feed reared individuals, Firmicutes reached the highest relative abundance (10-80%), followed by Proteobacteria (6-55%), Actinobacteria (1-31%) and Bacteroidota (0-22%). The rearing substrate was the main driver of microbiota composition, while the developmental stage influenced only whole individual’s bacterial microbiota composition. Gut regions were associated with distinct bacterial composition and richness, with the diversity decreasing along the digestive tract. For the first time, microeukaryotes of the microbiota other than Fungi were investigated using 18S genetic marker amplicon sequencing with novel blocking primers specific to the black soldier fly. Microeukaryotes are a neglected part of the multitrophic microbiota communities, that can have similar effect on their host like bacterial microbiota. Microeukaryotes from seven orders were identified in black soldier fly, including potential pathogens (e.g. Aplicomplexa group). Nucletmycea was the dominant class throughout development, followed by Holozoa and Stramenophiles. The eukaryote microbiota was structured by developmental stages but not by gut regions. Insights from this study are a steppingstone toward the microbiological optimization of black soldier fly for industrial rearing, highlighting how a synthetic microbiota assembly should be tailored to the rearing environment of the larvae at a targeted developmental stage.